Molecular iodine‐catalyzed N‐benzylation of anilines substituted by electron withdrawing groups. Issue 1 (25th February 2019) - Tram, Nguyen Thi Thu; Dat, Tong Ho; Phong, Truong Hoai; Dam, Nguyen Phuc; Tuan, Nguyen Trong
Abstract: Fourteen derivatives of N ‐alkylated anilines bearing electron withdrawing group from available aryl alcohols and the parent N ‐unsubstituted aniline using iodine‐catalyst were synthesized throughout a convenient and green protocol, in which three derivatives were previously unreported compounds. The structures of these compounds were elucidated by HRMS, NMR spectral data and in comparison with the literature.